Bifunctional Dimethyldichlorosilane Assisted Air‐Processed Perovskite Solar Cell with Enhanced Stability and Low Voltage Loss. Issue 5 (12th January 2023) - Zhou, Peng; Lu, Shaojuan; Mo, Yanping; Cheng, Jiahao; Jiao, Chuanjia; Zhang, Xiao-Li; Li, Wangnan; Liang, Guijie; Wang, Jingyang; Huang, Fuzhi; Cheng, Yi-Bing
Abstract : As perovskite solar cells (PSCs) are sensitive to moisture, they cannot be prepared in the open air, which increases manufacturing costs. To address this issue, bifunctional dimethyldichlorosilane (DMDCS) is employed as both an additive and capping layer to passivate the grain boundaries and surfaces of MAPbI3 perovskite films, thus inhibiting water erosion. Accordingly, the preparation of highly efficient PSCs in an air atmosphere is realized. Herein, the passivation mechanism of DMDCS on the perovskite film and the interface is analyzed by investigating photoexcited carrier mobility and ultrafast transient adsorption spectroscopy (TAS). An improvement of charge‐carrier diffusion, featuring an enhanced lifetime from 7.62 to 11.22 ps by the precursor doping, is exhibited in the results of TAS. The charge‐carrier extraction at the interface is also greatly promoted, with the decreased decay time from 0.29 to 0.16 ns by surface passivation, consistent with the carrier mobility via space charge‐limited current. Finally, the modified devices achieve an exceptional efficiency of 20.69%, and demonstrate long‐term environmental stability, maintaining more than 80% of the initial efficiency after 1000 h in ambient at a relative humidity of 40% without encapsulation. Abstract : Herein, dimethyldichlorosilane (DMDCS) is used to passivate the grain boundaries and surfaces of MAPbI3 perovskite films during its fabricating in air, achieving an excellent power conversion efficiency of 20.69%. The perovskite solar cells with the DMDCS modification retain 80% of the initial efficiency after 1000 h in ambient without encapsulation (air environment at relative humidity of 40%–50%).